Penyalahgunaan Bilyet Giro Sebagai Alat Pembayaran - Syalshabilla Andi Puteri; Risma Seli Novitasari; Sumriyah Sumriyah (Universitas Katolik Widya Karya Malang, 2023)
Giro is a modern payment instrument that is currently very widely used in Indonesia because of the ease and security of transactions of buying and selling in a large amount of money. With the Giro masyarakar no longer worry so much money when buying and selling transactions. But because of weak laws governing the Giro, the system of banking that is not good to make Giro much abused in the world trade in Indonesia as ever used for fraud, breach of contract and even being sold paper giro already closed the account but not withdrawn by the Bank concerned, here the Bank's role is very important, but in reality only a Bank Account provider or manager of the Giro and only a block accounts Giro Giro when the Kosong.pengadilan also in deciding the case on the Giro this could happen fault and most of the cases the Giro go to the District Court of the plaintiff's money is not returned and the plaintiffs continue to experience losses. This is what makes Giro is irrelevant used as means of payment in Indonesia.